ANALISIS PENGARUH JUMLAH PENDUDUK, PRODUK DOMESTIK REGIONAL BRUTO, TINGKAT INFLASI DAN JUMLAH LUAS LAHAN TERHADAP PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB) DI EKS KARESIDENAN SEMARANG (Students' Journal of Accounting and Banking, 2015)
Land and Building Tax is a tax imposed on land and building objects. Land and Building Tax is one form of taxation that has good potential for development financing therefore the management of the land and building tax becomes important. The purpose of this study was to analyze the influence of population, Gross Domestic Product, inflation rate and the amount of land area of the land and building tax receipt Ex residency in Semarang. These factors affect the increase in Tax Object Sale Value Tax on Land and Building, by increasing the Tax Object Sale Value of Land and Building Tax revenues will also increase. The population used in this study is the residency of Semarang and ex sample in this study is Semarang District, Kendal, Demak, Grobogan, Salatiga and Semarang with the data from 2006 to 2012. The selection of the sample in this study using a sample saturated. The type of data used are secondary data using methods of documentation and literature. The analytical tool used is multiple linear regression. These results indicate a variable number of population and GDP significantly influence the acceptance of land and building tax residency in Ex Semarang, meaning that any increase in population and GDP will improve also the land and building tax receipts in Ex residency of Semarang. While variable rate of inflation and the amount of land area did not significantly influence the acceptance of land and building tax residency of Semarang in Ex.Keywords: Land and Building Tax, Total Population, GDP, Inflation and Total Land Area